The Influence of Governance and Political Support on Corrupt Practices in Aceh Province - Muhammad Hasbi Arifuddin; Werry Darta Taifur; Fajri Muharja (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The study investigates how governance and political support affect the level of corruption in Aceh Province. To measure the level of corruption, the number of corrupt individuals involved in corruption cases that the court handled between 2019 and 2021 was taken into consideration. The governance aspect was evaluated based on the achievements of Monitoring Control for Prevention (MCP) and performance accountability, while political support was assessed by the support provided by political parties in the legislature to regional leaders. The negative binomial panel regression method with a fixed-effect approach was used to analyze the data collected from 24 local governments (provincial and district/city) in Aceh Province. The results indicate that governance has a significant negative impact on corruption. Therefore, it is crucial to consistently improve governance by enhancing MCP achievements and performance accountability in local governments to combat corruption in Aceh Province. Improvement efforts can be made to optimize the role of APIP in overseeing the implementation of government, especially state financial management to be more effective and efficient